Disentangling Internal and External Contributions to Atlantic Multidecadal Variability Over the Past Millennium - Fang S. -W.; Khodri M.; Timmreck C.; Zanchettin D.; Jungclaus J. (Geophysical Research Letters, 2021)
The Atlantic multidecadal variability (AMV) modulates the North Atlantic surface ocean variability and affects decadal climates over the globe; its underlying mechanisms remain, however, under debate. In this study, we use a multi-model ensemble of transient past-millennium (850–1849) and unperturbed preindustrial control simulations contributing to the paleoclimate modeling intercomparison project—phase 4 (PMIP4) to decompose the AMV signal into the internal AMV and the external signal. The internal component of AMV exhibits no robust behavior across simulations during periods of major forcing such as strong volcanic eruptions, whereas the external forced temperature responds to volcanic eruptions with an immediate radiative cooling followed, in some simulations, by a sequence of damped multidecadal oscillations. The internal component tightly relates with the Atlantic meridional overturning circulation (AMOC) and dominates the fluctuations of AMV; whereas the external signal has limited impacts on AMOC and explains ∼25% of the AMV variance over the past millennium.